2017
DOI: 10.1038/celldisc.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex gene regulation by CRISPR-ddCpf1

Abstract: The clustered regularly interspaced short palindromic repeats (CRISPR)/dCas9 system has been widely applied in both transcriptional regulation and epigenetic studies. However, for multiple targets, independent expression of multiple single guide RNAs (sgRNAs) is needed, which is less convenient. To address the problem, we employed a DNase-dead Cpf1 mutant (ddCpf1) for multiplex gene regulation. We demonstrated that ddCpf1 alone could be employed for gene repression in Escherichia coli, and the repression was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
186
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(209 citation statements)
references
References 53 publications
10
186
0
Order By: Relevance
“…Next, we sought to demonstrate the ability of multiplex gene regulation of the CRISPR-dCpf1 system. As the targeting of multiple genes has been demonstrated in several recent studies (17,18,20), and a single bound dCpf1, without dedicated inactivation domains, was not sufficient in suppressing gene expression in human HEK293T cells (20), we studied gene repression by tandemly positioned dCpf1 roadblocks within a single gene. Guide sequences were selected to target three independent segments within the coding region of the sf-gfp gene.…”
Section: Enhanced Gene Repression Through Multiplex Targeting Of Dcpf1mentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we sought to demonstrate the ability of multiplex gene regulation of the CRISPR-dCpf1 system. As the targeting of multiple genes has been demonstrated in several recent studies (17,18,20), and a single bound dCpf1, without dedicated inactivation domains, was not sufficient in suppressing gene expression in human HEK293T cells (20), we studied gene repression by tandemly positioned dCpf1 roadblocks within a single gene. Guide sequences were selected to target three independent segments within the coding region of the sf-gfp gene.…”
Section: Enhanced Gene Repression Through Multiplex Targeting Of Dcpf1mentioning
confidence: 99%
“…Although aspects of the CRISPR-Cpf1 system as DNA endonuclease has been characterized, there have been only first attempts in using CRISPR-dCpf1 as transcriptional regulators. These studies proved its applicability in bacterial, plant, and mammalian cells (17)(18)(19)(20). To harness and streamline the system for multiplex gene regulation, three specific aspects need addressing or systematic characterization: 1. a mutational scheme that abolishes Cpf1's nuclease activity and yet minimally affects its DNA binding and RNase activities; 2. the requirements for pre-crRNA that contains multiple direct repeat-guide sequence units for efficient crRNA processing and DNA targeting (14,21); and 3. the dependence of DNA binding strength on the PAM sequence (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Cas12a is so far the smallest CRISPR system with dual DNase and RNase activity [45]. Interestingly, a DNase‐dead version of Cas12a with the amino acid exchange E993A termed ddCas12a (or ddCpf1) [46] preserved the RNase activity, but lacked DNAse activity. Therefore, ddCas12a in theory can be employed to process its precursor crRNA as well as a customized CRISPR array [45,46].…”
Section: Establishment Of Crisprimentioning
confidence: 99%
“…Recent studies demonstrated that DNase-dead Cas12a can also be used for gene regulation in bacteria and plants (Tang et al, 2017; Zhang et al, 2017), suggesting that a wider range of applications will also be enabled by dCas12a.…”
Section: Applications Based On Type V and Vi Systemsmentioning
confidence: 99%